Synthesis and Antibacterial Activity of Some Novel Schiff S-Bases Compounds Containing Oxadiazole Ring - Tomma, J. H.; Raheema, A. H.; Rouil, I. H. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2019)
Condensation of 4-methoxybenzoyl hydrazine with 4- aminobenzoic acid in the presence of POCl3 gave the oxadiazole derivative [III] .This compound was demethylated with aluminium chloride to give series of 2- (4-hydroxy phenyl)-5-(4-amino phenyl) 1,3,4-oxadiazole [IV]. Series of Schiff s bases [V]n were synthesized by the condensation of compound [IV] with 4-n-alkoxy benzaldehyde in the presence of glacial acetic acid. Condensation of compounds [VI]n. with adipoyl chloride in dry pyridine leads to the formation of a new homologous series [VI]n. The structures of the synthesized compounds were confirmed by physical and spectral means The new compounds [VI]n have been screened for their antibacterial activities . The results showed considerable antibacterial activity against Escherichia Coli (G-),but did not show any antibacterial activity against Staphylococcus aureus (G+)